Investigation of the carbon dioxide adsorption behavior and the heterogeneous catalytic efficiency of a novel Ni-MOF with nitrogen-rich channels. Issue 50 (12th August 2020) - Aryanejad, Sima; Motlagh, Naser Valipour
Abstract : MOFs have attracted remarkable attention as solid sorbents in CO2 capture processes for their low-energy post-combustion. Abstract : MOFs have attracted remarkable attention as solid sorbents in CO2 capture processes for their low-energy post-combustion. In this paper, a new Ni-based MOF, Ni4 (TATB)1.5 (EtO)3.5 (NEt3 )4, was synthesized and characterized using various physicochemical techniques. The efficiency of the as-prepared Ni-MOF as a solid sorbent for CO2 capture was investigated, and acceptable adsorption was exhibited. Furthermore, this Ni-MMOF was used as a catalyst in toluene selective oxidation, for eliminating a volatile organic compound, with tert -butyl hydroperoxide as an oxidant in the absence of organic solvents. The obtained results indicated that Ni-MOF has good catalytic activity and could be reused three times without considerable loss of its catalytic activity. This study highlights the great potential of developing MOFs to achieve green chemistry goals with the removal of hazardous liquid and gas compounds such as toluene and CO2 .